Hubungan Tingkat Pengetahuan dan Perilaku Penggunaan Obat Batuk Secara Swamedikasi Pada Mahasiswa Universitas Bali Dwipa - Kamalia Kondo (STIKes Ibnu Sina Ajibarang, 2025)
Self-medication is an effort made by the community to overcome minor complaints that are often experienced by the community, so the role of self-medication cannot be ignored. Students need to have good knowledge to obtain the right behavior in self-medication. This study aims to determine the relationship between the level of knowledge and behavior of using cough medicine by self-medication in Bali Dwipa University students. This study is an observational study with a cross-sectional design. Sampling with consecutive sampling technique using a questionnaire. The sample used was 35 sampelts. This research was conducted in June-July 2024. The data analysis used was the Chi-Square analysis model with SPSS version 25. The results of this study showed that 62.86% of students had a high level of knowledge of cough self-medication, and the behavior of using cough medicine showed that 78.43% of students had good behavior. There is a significant relationship between the level of knowledge and behavior of using cough medicine with a significance value of 0.001 (<0.05).